PENCARUH KOSENTRASI EKSTRAK BIJI KARET (Havea brancilliensis Muel, ARG) SEBAGAI PEMBIUS TERHADAP AKTIVITAS DAN KELULUSAN HIDUP IKAN MAS (Cyprinus carpio, L) SELAMA TRANSPORTASI - Sukmiwati, Mery; Sari, N. Ira (Fakultas Perikanan dan Kelautan Universitas Riau, 2007)
A research study was carried out from September 2004 to February 2005. Theresult showed that the best concentrate from rubber seed extract were 5.4 mg/Ienable to transport the fish for 8 hours producing 90 % survival rate, withconcentrate 5.4 mg/1 to sped up anesthesis time were 10 – 15 minutes, withconcentrate 5.4 mg/I at temperature of 14°C indicated that the best condition offish after anesthesis.